What is Involved in the Concept of a Phoneme - Jelaska, Zrinka (Array, 2004)
The phonology of a language, operating on its own principles of organisation, is a cognitive phenomenon as well as semantic structure. However, the Cognitive Grammar literature on phonological issues is incomparable to the semantic ones. It is even more sparse when phonology of Slavic languages is concerned. This paper deals with the category of phonemes, their prototypical and other members, as well as the contribution of various linguistic levels and cognitive issues which play a role in extracting the phoneme shame of a particular language. The data drawn mainly from Croatian language will show how phonemes are defined by universal acoustic and articulatory characteristics of human sounds in relation to language specificities, as well as the function they serve or may serve in a particular language. Language contact shows how cross-comparison could attribute to understanding the principles operating in the phonemic inventory. For example, Slovak speakers usually have the same problems as Hungarian when acquiring Croatian palatal lateral aproximant due to the writing rules, although Slovak has the same phoneme, which Hungarian lacks. Such cases show that the writting-systems play a role in the phonemic conceptualisation as well, enabling linguists to have a better understanding why some orthographic issues cause so much emotional response from ordinary speakers of the language, e.g. the presence or absence of letters -j- or -i- in names such as Mia, G Mije, words such as biel / bijel / bjel (white), vidjeti / vidieti (to see).